Penguatan Branding Digital Perajin Perak Celuk melalui Program Back to Roots #9: Penelitian - A.A. Sg. Candra Permatasari; Ni Putu Ayu Pirdayanti (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Celuk Village in Gianyar is widely recognized as a center of high-quality silvercraft production; however, the challenges of digital marketing limit craftsmen’s ability to expand their market reach. The community service program “Back to Roots #9: Hope in Silver Piece” was conducted to enhance the digital branding capabilities of craftsmen and local youth through training on modern marketing strategies. This program integrates the marketing mix theory (Kotler & Keller, 2016), brand identity concepts (Aaker, 1996), and digital marketing frameworks (Chaffey, 2019). Methods included sharing sessions, hands-on video branding production, and school-based socialization. The results indicate improved understanding and skills among participants in applying digital branding and producing promotional content. This program contributes significantly to digital literacy and the strengthening of Celuk’s silvercraft product identity.